Integrated continuous biomanufacturing on pilot scale for acid‐sensitive monoclonal antibodies. Issue 8 (7th May 2022) - Schwarz, Hubert; Gomis‐Fons, Joaquín; Isaksson, Madelène; Scheffel, Julia; Andersson, Niklas; Andersson, Andreas; Castan, Andreas; Solbrand, Anita; Hober, Sophia; Nilsson, Bernt; Chotteau, Veronique
Abstract: In this study, we demonstrated the first, to our knowledge, integrated continuous bioprocess (ICB) designed for the production of acid‐sensitive monoclonal antibodies, prone to aggregate at low pH, on pilot scale. A high cell density perfusion culture, stably maintained at 100 × 10 6 cells/ml, was integrated with the downstream process, consisting of a capture step with the recently developed Protein A ligand, ZCa ; a solvent/detergent‐based virus inactivation; and two ion‐exchange chromatography steps. The use of a mild pH in the downstream process makes this ICB suitable for the purification of acid‐sensitive monoclonal antibodies. Integration and automation of the downstream process were achieved using the Orbit software, and the same equipment and control system were used in initial small‐scale trials and the pilot‐scale downstream process. High recovery yields of around 90% and a productivity close to 1 g purified antibody/L/day were achieved, with a stable glycosylation pattern and efficient removal of impurities, such as host cell proteins and DNA. Finally, negligible levels of antibody aggregates were detected owing to the mild conditions used throughout the process. The present work paves the way for future industrial‐scale integrated continuous biomanufacturing of all types of antibodies, regardless of acid stability. Abstract : A high cell density perfusion process, performed at pilot scale in 30 L bioreactor, was integrated with a continuous purification process including a Protein A capture using ZCa ligand with mild pH elution, a solvent/detergent‐based virus inactivation and two polishing steps, cation and anion exchange. This completely automated process generated purified antibody at very high yield with no detectable aggregation.